SOSIALISASI PENANGGULANGAN TINDAK PIDANA ASUSILA DAN NARKOBA DI KOTA PADANG PANJANG - Aria Zurnetti; Maulana Fajri Adrian (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
Children are gifts by God Almighty given to parents as successors and hope for the future of a nation. Children as human beings who are weak and vulnerable to the threat of crime must receive attention and protection. However, not many parents know the dangers, types, and sanctions of immoral and drug crimes and the appropriate steps in overcoming them. The purpose of the activity is to socialize the dangers, types, and sanctions of immoral crimes and drugs and increase legal awareness in particular to Dharma Wanita Padang Panjang City to play a role in overcoming immoral crimes and drugs in children both preventively and repressively. The activity method is in the form of socialization, introduction, simulation, and finally evaluation by distributing questionnaires to the participants. The targets of the Dharma Wanita activities are the Padang Panjang City Government, Bundo Kanduang, Family Welfare Development group, representatives from elementary, middle, and high schools. The results of the activities obtained are that children's development of the current era causes easy internet access. It can be an opportunity for immoral crimes and drug abuse against children if there is no or weak supervision by adults. After the socialization activities were carried out, there was an increase in the knowledge of the Dharma Wanita of Padang Panjang City about the dangers, types, and sanctions of immoral and drug crimes and appropriate steps in tackling them both preventively and repressively. Besides that, there is a robust Nagari adat kinship system, the principle of deliberation/consensus, and the influence of DharmaWanita's role is considered to have potential in overcoming cases of immoral crimes and drug abuse among children. Furthermore, it is recommended for parents to supervise children when using gadgets so that children avoid threats/dangers from immoral and narcotics crimes.